Numerical Analysis of Aspect Ratio Effects on the Mechanical Behavior of Perforated Steel Plates - Thiago da Silveira; Eduardo Araujo Crestani; Elizaldo Domingues dos Santos; Liércio André Isoldi (Metals, 2025)
Thin plates are commonly used in mechanical structures such as ship hulls, offshore platforms, aircraft, automobiles, and bridges. When subjected to in-plane compressive loads, these structures may experience buckling. In some applications, perforations are introduced, altering membrane stress distribution and buckling behavior. This study investigates the elasto-plastic buckling behavior of perforated plates using the Finite Element Method (FEM), Constructal Design (CD), and Exhaustive Search (ES) techniques. Simply supported thin rectangular plates with central elliptical perforations were analyzed under biaxial elasto-plastic buckling. Three shapes of holes were considered—circular, horizontal elliptical, and vertical elliptical—along with sixteen aspect ratios and two different materials. Results showed that higher yield stress leads to higher ultimate stress for perforated plates. Regardless of material, plates exhibited a similar trend: ultimate stress decreased as the aspect ratio dropped from 1.00 to around 0.40 and then increased from 0.35 to 0.25. A similar pattern was observed in the stress components along both horizontal (x) and vertical (y) directions, once the y-component became considerably higher than the x-component for the same range of 0.40 to 0.25. For longer plates, in general, the vertical elliptical hole brings more benefits in structural terms, due to the facility in the distribution of y-components of stress.